Identification and classification of commercially relevant per‐ and poly‐fluoroalkyl substances (PFAS). (22nd June 2021) - Buck, Robert C.; Korzeniowski, Stephen H.; Laganis, Evan; Adamsky, Frank
Abstract: Per‐ and poly‐fluoroalkyl substances (PFAS) are a universe of fluorinated organic substances with very different physical, chemical, and biological properties including polymers and non‐polymers; solids, liquids, and gases. Commercial PFAS‐based products have been used in a wide variety of industrial and consumer applications because they have unique performance properties of significant socioeconomic value. The PFAS definition has evolved and expanded over the years. Numerous lists of PFAS, some with thousands of entries, have been compiled, but none have clearly identified which of the substances are commercially relevant. This study is the first to use a bona‐fide "bottom up" approach to identify how many of the 4730 PFAS substances listed in a 2018 OECD/UNEP Report are directly connected to commercial products based on input from three major global producers. This study provides new and valuable insight into the 2018 OECD/UNEP Report list of PFAS substances. The results show that 256, less than 6%, of the 4730 PFAS substances presented in the 2018 OECD/UNEP Report are commercially relevant globally. This study suggests that grouping and categorizing PFAS using fundamental classification criteria based on composition and structure can be used to identify appropriate groups of PFAS substances for risk assessment, thereby dispelling assertions that there are too many PFAS chemistries to conduct proper regulatory risk assessments for the commercially relevant substances. Integr Environ Assess Manag 2021;17:1045–1055. © 2021 The Chemours Company, Beach Edge Consulting, LLC, AGC Chemicals Americas Inc., Daikin America Inc. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC). KEY POINTS: This study is the first to use a bona‐fide "bottom up" approach to identify how many of the 4730 PFAS substances listed in a 2018 OECD/UNEP Report are directly connected to commercial products based on input from three major global producers. The study results show that 256, less than 6%, of the 4730 PFAS substances presented in the 2018 OECD/UNEP Report are commercially relevant globally. This study suggests that grouping and categorizing PFAS using fundamental classification criteria based on composition and structure can be used to identify appropriate groups of PFAS substances for risk assessment.